Hilbert-Huang transform based transient analysis in voltage source converter interfaced direct current system - Li, Dongyu (2022)
Due to the rapid discharging of the dc-link capacitors, the short-circuit fault normally results in a fast-growing transient current in the voltage source converter (VSC) based dc power system. Therefore, a fast and sensitive fault detection method is required. In this article, the feasibility of Hilbert-Huang transform (HHT) for fault detection in VSC-based high-voltage direct current systems is analyzed. The instantaneous energy density level is used as the fault detection criterion, which emphasizes the fault characteristics in a predefined frequency range and suppresses the effect of steady-state ripple components. The theory of the proposed HHT-based fault detection method is presented in detail. Its effectiveness is tested on an OPAL-RT based multiterminal dc system and a point-to-point experimental dc system. A response delay within 2 ms after the fault inception is achieved. The comparison with other popular frequency-domain based fault detection methods including the wavelet transform, the short-time Fourier transform, the S transform, and the existing HHT-based analysis, using amplitude frequency coefficient as detection criterion, underlines the performance of the proposed method.